Sistem Informasi Presensi Karyawan Berbasis Android (Studi Kasus: Asuransi Panin Dai-Ichi Life) - Tasya Rizki Ramadhini; Fenty Ariany; Akhmad Jayadi (Jurnal Teknologi dan Sistem Informasi, 2023)
Mobile technology was Mobile technology was technology in mobile phone or smartphone which was digital. By using this technology, all users were integrated with each other. One of the most famous mobile operating systems was Android, which included the Google Positioning System (GPS) feature. Utilize GPS to find out where employees. So that GPS could be used as a tool to create an Android-based Employee Attendance Application at Panin Dai-Ichi Life Insurance, which aimed to speed up the attendance and attendance report process. In building this application design using the waterfall method where there were stages of Analysis, Design, Coding and Testing. This application implemented GPS using the geofence method to detect the position of the dividend when making attendance and the Haversine Formula method to determine the radius distance that could be done attendance. This test used Black box testing where the functional side was already functioning properly.